Reproducibility of measuring amniotic fluid index and single deepest vertical pool throughout gestation. (28th March 2015) - Sande, J. A.; Ioannou, C.; Sarris, I.; Ohuma, E. O.; Papageorghiou, A. T.
Abstract Objective The aim of this study is to assess the intraobserver and interobserver reproducibility of measurement of amniotic fluid index (AFI) and single deepest vertical pool (SDVP), also known as the maximal vertical pocket. Methods A total of 175 fetuses were evaluated. For each fetus, two observers acquired duplicate sets of AFI and SDVP. Measurement differences were expressed as actual and percentage values. For all comparisons, Bland–Altman plots were used to compare differences, and limits of agreement were calculated. Results Intraobserver and interobserver agreement remained fairly constant with gestation, both for AFI and SDVP. The intraobserver limits of agreement for AFI were −5.2 to 5 cm or −39% to 37%; whereas for SDVP, these were −2.6 to 2.4 cm or −52% to 48%. The interobserver limits of agreement for AFI measurement were −7.3 to 7.1 cm or −54% to 53% and for SDVP measurement were −2.5 to 2.5 cm or −51% to 52%. Intraobserver coefficient of variation for SDVP was 14% and for AFI was 19%; the interobserver coefficient was 19% for both AFI and SDVP. Conclusion Limits of agreement for both methods are wide. The choice of method should be dictated by clinical considerations other than method reproducibility. © 2014 John Wiley & Sons, Ltd.